Brazil is getting older: demographic changes and epidemiological challenges Envelhecimento populacional do Brasil: mudanças demográficas e desafios epidemiológicos - Renato P. Veras (Universidade de São Paulo, 1991)
Population ageing is currently a phenomenon not only in developed countries but also in third world countries. In this paper the features of a population's ageing and the process of epidemiological transition are discussed along with the worldwide changes in age-structure. Population statistics in Brazil and the characteristics of the elderly population are presented and analysed in the light of recent changes. The Brazilian elderly population is also discussed, particularly the issues relating to the social cost of the aged population, its urban and rural distribution, the elderly by sex, marital status and level of schooling, and emphasis is given to the imbalance of the sexes and the consequences of it for women. O crescimento da população idosa é um fenômeno que ocorre nos países centrais, mas também, de modo crescente, nos países do Terceiro Mundo. Este artigo apresenta os motivos deste crescimento, discute o processo de transição epidemiológica, as mudanças na estrutura etária da população idosa em todo o mundo, e em particular no Brasil. Estatísticas da população brasileira e as características do idoso brasileiro são apresentadas e analisadas em função das mudanças ocorridas recentemente. O artigo aborda vários tópicos relacionados com o idoso brasileiro: o custo financeiro para a sociedade manter uma população idosa, a distribuição urbana e rural, a diferença numérica entre sexos, o estado conjugal, a escolaridade, entre outros. Ênfase é conferida a algumas características e particularidades da mulher idosa.